Make Brilliant Work : Lesson on Creativity, Innovation, and Success - Judkins, Rod (London Pan Books, 2022)
You don$1 (Bt have to be brilliant to produce brilliant work. Make Brilliant Work will show you the methods and techniques other people have used and how you can use them too.s
Including Illustration, Bibliography And References
Keywords: Success -- Creative ability -- Success in business